Carbon Supported Cu-Sn Bimetallic Alloy as an Excellent Low-Cost Cathode Catalyst for Enhancing Oxygen Reduction Reaction in Microbial Fuel Cell. Issue 9 (1st January 2018) - Noori, Md. T.; Bhowmick, G. D.; Tiwari, B. R.; Ghangrekar, O. M.; Ghangrekar, M. M.; Mukherjee, C. K.
Abstract : Cu-Sn bimetallic alloy supported on acetylene black was prepared and tested under different loadings per unit cathode surface area viz. 1 mg.cm −2, 2 mg.cm −2 and 5 mg.cm −2 as a catalyst to improve the oxygen reduction reaction (ORR) and to enhance performance of the microbial fuel cell (MFC). Electrochemical analyses were performed to evaluate the ORR kinetics. Results of cyclic voltammetry showed multiple redox current peaks for all the loadings of Cu-Sn with positive onset potential of ∼0.25 V. Among different loadings, cathode with Cu-Sn loading of 2 mg.cm −2 proved to be the best choice for application in MFC, due to less charge transfer resistance and high redox current. Power density and coulombic efficiency of 470 mW.m −2 and 36%, respectively, were obtained from MFC using Cu-Sn catalyzed cathode with a loading of 2 mg.cm −2, which was higher than the MFCs using cathodes with 1 and 5 mg.cm −2 of Cu-Sn loadings and it was even found slightly higher than the MFC using Pt-C catalyst on cathode. Power generation per unit cost of catalyst for MFC using Cu-Sn catalyst was found to be 11-fold higher than the MFC using Pt-C cathode, ascertaining former as low-cost cathode catalyst for harvesting more power from MFCs.